2022
DOI: 10.1101/2022.12.16.520784
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improved humoral immunity and protection against influenza virus infection with a 3D porous biomaterial vaccine

Abstract: New vaccine platforms that properly activate humoral immunity and generate neutralizing antibodies are required to combat emerging and re-emerging pathogens, including influenza virus. Biomaterial scaffolds with macroscale porosity have demonstrated tremendous promise in regenerative medicine where they have been shown to allow immune cell infiltration and subsequent activation, but whether these types of materials can serve as an immunization platform is unknown. We developed an injectable immunization platfo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 57 publications
2
3
0
Order By: Relevance
“…IgG1 antibodies closely matched total IgG titers, confirming the type 2 biased as previously shown ( Supplemental Fig. 1 ) (27). Furthermore, temporal analysis of a single titration from each group demonstrated that while the anti-RBD IgG levels from Alum(S) were higher than PBS(S), VaxMAP(S) had consistently elevated antigen-specific antibodies compared to both groups ( Fig.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…IgG1 antibodies closely matched total IgG titers, confirming the type 2 biased as previously shown ( Supplemental Fig. 1 ) (27). Furthermore, temporal analysis of a single titration from each group demonstrated that while the anti-RBD IgG levels from Alum(S) were higher than PBS(S), VaxMAP(S) had consistently elevated antigen-specific antibodies compared to both groups ( Fig.…”
Section: Resultssupporting
confidence: 88%
“…IgG1 antibodies closely matched total IgG titers, confirming the type 2 biased as previously shown (Supplemental Fig. 1) (27). Furthermore, temporal analysis of a single titration from each group demonstrated that while the anti-RBD IgG (which was not certified by peer review) is the author/funder.…”
Section: 3supporting
confidence: 85%
See 3 more Smart Citations